Immunohistochemical study of histone protein 3 modification in pediatric osteosarcoma identifies reduced H3K27me3 as a marker of poor treatment response. - Sebastian Kondratowski; Danielle Cohen; Rebecca J Deyell; Ash Sandhu; Jonathan W Bush (PLoS ONE)
The most common pediatric primary malignant bone tumor, osteosarcoma, is often described as genetically non-recurrent and heterogeneous. Neoadjuvant chemotherapy is typically followed by resection and assessment of treatment response, which helps inform prognosis. Identifying biomarkers that may impact chemotherapy response and survival could aid in upfront risk stratification and identify patients in highest need of innovative therapies for future clinical trials. Relative to conventional genetics, little is known about osteosarcoma epigenetics. We aimed to characterize the methylation and phosphorylation status in osteosarcoma using histone markers found in primary diagnostic biopsies and their paired metastases. We constructed two tissue microarray sets from 58 primary diagnostic samples and 54 temporally-separated but related metastatic or recurrent samples, with tissue blocks available from 2002-2022. Clinical charts were reviewed for post-therapy necrosis response, presence of metastatic disease or recurrence, and overall survival. We evaluated 6 histone H3 residues using immunohistochemistry, including H3K4me3, H3K9me3, H3K27me2, H3K27me3, H3S10T11phos, and H3S28phos. Tumors were scored with low (<25%) or high (≥25%) nuclear staining of tumor cells. Diagnostic biopsies with low H3K27me3 nuclear staining were associated with poor treatment response (≤90% necrosis) at the time of definitive excision (P<0.05). We observed loss of H3S10T11phos expression in metastatic and recurrent resections specimens compared to the primary tumor (P<0.05). Expression patterns for the remaining histone markers did not show significant associations with disease parameters or survival. Although larger cohort studies are needed, these results support the expanded evaluation of histone markers, particularly H3K27me3 and H3S10T11phos, in osteosarcoma biology and risk stratification.